Biological significance and prognostic relevance of peripheral blood neutrophil-to-lymphocyte ratio in soft tissue sarcoma - Chan, Jason Yongsheng; Zhang, Zewen; Chew, Winston; Tan, Grace Fangmin; Lim, Chloe Liwen; Zhou, Lingyue; Goh, Wei Lin; Poon, Eileen; Somasundaram, Nagavalli; Selvarajan, Sathiyamoorthy; Sittampalam, Kesavan; Chin, Francis; et al. (Scientific reports, 2018)
Peripheral blood indices of systemic inflammation such as the neutrophil-lymphocyte ratio (NLR) have been shown to be prognostic in various cancers. We aim to investigate the clinical significance of these indices in patients with soft tissue sarcoma (STS). Seven hundred and twelve patients with available blood counts at diagnosis and/or metastatic relapse were retrospectively examined. An optimal cutoff for NLR-high (>2.5) in predicting overall survival (OS) was determined using receiver operating curve analyses. Survival analyses were performed using the Kaplan-Meier method and multivariate Cox proportional models. Our results show that NLR was significantly higher in patients with distant metastasis at diagnosis (n = 183) compared to those without (n = 529) (median: 4.36 vs 2.85, p < 0.0001). Progression of localized disease at diagnosis to metastatic relapse within the same patients was associated with an interval increase in NLR (median: 3.21 vs 3.74, p = 0.0003). In multivariate analysis, NLR-high was the only consistent factor independently associated with both worse OS (HR 1.53, 95% CI 1.10–2.13, p = 0.0112) and relapse-free survival (HR 1.41, 95% CI 1.08–1.85, p = 0.0125) in localized disease, as well as OS (HR 1.82, 95% CI 1.16–2.85, p = 0.0087) in metastatic/unresectable disease. In conclusion, high NLR is an independent marker of poor prognosis among patients with STS.